Effects of Mould Rotation on Element Segregation and Compact Density of Electroslag Ingots during Electroslag Remelting Process - Chang, Lizhong; Shi, Xiaofang; Wang, Runxi; Cong, Junqiang (High temperature materials and processes, 2015)
Steel solidification process control, especially in the solidification process of high-alloy steel, and improving the solidification structure have been increasingly gaining interest among metallurgists, particularly the electroslag workers. To further develop the electroslag remelting (ESR) process and to improve the ingot solidification structure, the effects of mould rotation on chemical element distribution and the compact density were investigated in this study. The experimental results showed that chemical element distribution would become more uniform when the mould keeps the reasonable rotation rate. However, the excessive rotation rate would deteriorate the solidification structure of steel. When mould rotation rate was between 0 and 28 r/min, maximum segregation of carbon could decrease from 3.19 to 1.084, and statistical segregation decreased from 0.2636 to 0.0554. Maximum segregation of chromium could decrease from 1.316 to 1.131, and statistical segregation decreased from 0.2753 to 0.0657. The compact density increased from 0.7693 to 0.94. But element segregation would become bigger and compact density would become smaller if rotation rate further increased. The improvement in the solidification structure could be attributed to reasonable mould rotation rate which could initiate movement in the slag pool and further increase the uniformity of the temperature in the slag pool. At the same time, the movement in the slag pool could also affect the metal molten droplet, scattering the liquid drop randomly in the metal pool. But the excessive rotation rate made the slag pool violent motion, so as to drive the molten metal pool to rotate which would carry off enriched steel surrounding the dendrites in the mushy zone and reduce the solute content in the region. As a result, the element segregation would occur.